ICT Revolutions in the Banking Sector of Nigeria: Determinants of E-Payment Channels By Customers - Chidiebere U. Enukoha; Pius U. Angioha; Chioma Mba; Abdulrasheed A. Abdulraheem (PT Mattawang Mediatama Solution, 2022)
Over two decades, the banking industry in Nigeria has been experiencing unprecedented ICT revolutions. These dynamics are reshaping and remodeling the entire sector. It is revolutionizing traditional banking methods using e-banking as an excellent tool for driving fast financial transactions. E-banking offers tremendous transaction opportunities to customers. This study examined factors that determine customers' choice of e-banking platform in Nigeria. The predictors considered here are Usefulness, reliability, ease of use and security. The study used a survey method. The sample size was determined using Survey Monkey Sample Size Determinant Technique at 3.3 margin error with 95 per cent confidence level. Semi-structured interview and questionnaire to retrieve data from participants. Elucidated data was analyzed using descriptive and parametric statistics. Results revealed that 71.5 per cent of the participants reported that electronic payment channel was easy to use, 99.5 per cent reported the Usefulness of electronic payment channel. Only 27.9 said that electronic payment channels are secured and safe. Again, 47.7 per cent reported that the electronic payment channel was reliable. From the parametric statistics carried out, the result revealed that Usefulness, security, ease of use and reliability are significant drivers of e-payment channels. The study recommends a need for the banks, fintech, financial and regulatory agencies to put in place structures and resources that will help improve the safety of the platforms and their reliability.